“Umah Macuy” Sebagai Center Of Learning Masyarakat Tertinggal Desa Napallicin Kecamatan Ulu Rawas Kabupaten Musi Rawas Utara - Gusti Aldo Wijaya; Euis Nur Af’idah; Wulan Utami Triyani; Ines Sr; Femi Wulandari; Desti Sia Mita; Kokoh Padli; Rinaldi Akbar; Ari Nopriansyah; Ahmad Riki; Mauliza Risma; Awang Wahyu Sadewa; Ngatijah; Yogi Rosa Putra; Nindia Saputri (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Napallicin Village is one of the underdeveloped villages located at the end of North Musi Rawas Regency with access only by one land access route, Tanah Merah, which takes ±4-5 hours. In addition to difficult access, the community's economy is still below the minimum wage and there is also no internet network that functions to upgrade knowledge. Based on the results of observations and interviews with the village head and the people of Napallicin Village, it is known that education in this village is categorized as low because 85% of the community, especially teenagers and the elderly, are illiterate because they do not go to school and the highest is only elementary school graduates. The low level of parental education, of course, affects the motivation to go to a further level. This problem is exacerbated by the fact that the educators who teach in schools are not in accordance with their competence and also the number is still very minimal. This certainly has an impact on the lack of literacy skills of children, adolescents and the elderly. Therefore, one of the solutions offered is "Umah Macuy" as a Center of Learning for Disadvantaged Communities in Napallicin Village, Ulu Rawas District, North Musi Rawas Regency". The objectives of this activity are 1) to improve literacy skills among children, adolescents and the elderly; and 2) the establishment of 5 literacy corners as centers of learning. The methods used are socialization, implementation, and evaluation. The result of this activity is that there is an increase in literacy skills, especially for the elderly in Napallicin Village. This increase can be seen from the literacy skills which were initially still lacking, which has increased in view of the results of the autobiography that was made. The conclusion that can be drawn is that the presence of Umah Macuy can be a means to help improve the literacy skills of the disadvantaged people of Napallicin Village.